Circularity Assessment: Macro to Nano Accountability Towards Sustainability - Patil, Rashmi Anoop; Ramakrishna, Seeram (Springer Nature, 2023)
This open access book attempts to provide a perspective on the circularity assessment at different levels of the systemic hierarchy and advocates better resource management for a sustainable future. It demonstrates how relevant circularity indicators are used for quantifying the extent of circularity of each level. Illustrative case studies that discuss the process of quantitatively interpreting progress towards circularity are provided. This work caters to a broad readership inclusive of governance, basic research, engineering, and business stakeholders. The conclusion signifies the role of consumer community in achieving circularity.